Multicomponent Diffusion during Osmotic Dehydration Process in Melon Pieces: Influence of Film Coefficient. Issue 4 (3rd March 2014) - Angilelli, Karina G.; Orives, Juliane R.; da Silva, Hágata C.; Coppo, Rodolfo L.; Moreira, Ivanira; Borsato, Dionisio
Abstract The water loss and sugar gain modeling during the dehydration process is useful as a technique for predicting the operating conditions and the process time. The transfer of sucrose and fructooligosaccharides (FOSs) to melon and water to solution was modeled based on generalized form of Fick's second law for simultaneous diffusion and resolved by the finite element method using the software package COMSOL Multiphysics 3.2. The diffusion coefficients, the mass transfer coefficient and the Biot number were determined using the simplex optimization method by minimizing the percentage errors. The optimized main diffusion coefficients were 21.07 × 10−11 m2/s for sucrose, 15.60 × 10−11 m2/s for water and 8.96 × 10−11 m2/s for FOS. The simulation results exhibited good fits to the experimental values, which validates the model predictive ability. The developed system for diffusion simulating water and solutes will enable control and modulation of the sucrose and FOS content in melon pieces. Practical Applications The use of functional sugars in fruits generates a new range of food taking into account the growing consumer market of these products. The study of processes involved in osmotic dehydration, as well as mass transfer simulation and modeling, is a useful predictive tool for the food industry, for assisting in the process time optimization among other variables involved.